The Evolution of Artificial Intelligence in Informatics - Muradova Kamola Akramjonovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2023)
Artificial Intelligence (AI) in informatics has evolved remarkably, transforming from basic algorithms to advanced systems capable of learning and adapting. This evolution is marked by significant milestones such as the development of neural networks, machine learning, and AI ethics. The impact of AI on various sectors, including healthcare, finance, and automation, reflects its growing sophistication. This article explores AI's progression, focusing on technological advancements, ethical considerations, and future implications.